Os instrumentos de incentivo à produção e uso de biodiesel no Brasil: uma análise constitucional sob o princípio do desenvolvimento sustentável - Ferreira, Ana Mônica Medeiros (2010)
The recent insertion of biodiesel derived from oily vegetables in the Brazilian energetic matrix calls for the study of some aspects that belong to it. The analysis of the carbonized energetic pattern concerns the paradigm of economic development that is constitutionally enshrined sustainable development which make environmental protection compatible with the needs of the economic rationality. This text is structured according to the ideas of modern hermeneutic that sees substantial value in the principles capable of create a harmonious relationship between law and society. The study of the constitutional principles to conduct a legal analysis about the National Program for Production and Use of Biodiesel - PNPB. The aim of the research is the study of PNPB ahead with the constitutional principles governing the economic order. To achieve this end we studied the sustainable development as a constitutional principle. We start with the notion that the thematic principles, and fundamental to understanding the dimension of sustainable development institute, since its concept is closely related to the applications of the principles enshrined in virtually all the constitutional order of the Western world. Then this was the National Energy Policy, initiating the approach by guiding principles of the National Energy Policy to develop the theme of public policy in the energy sector. Therefore, we studied the National Program of Biodiesel Production and Use - PNPB. From a technical introduction to the concept of biodiesel and a brief historical background, analyzing their advantages compared to fossil fuels predominantly used. Then it became a regulatory overview of the Brazilian legislation on the subject, central to understanding the plans and objectives pursued by the Brazilian government with encouraging the production of biodiesel. Finally discussed the tax incentives for production and use of biodiesel in Brazil. From the idea of federalism, characterized the tax as an instrument of state intervention in the economy. And finally it brought the tax incentives of Law No. 11.116/2005 in the face of the constitutional principles of economy and tax, and tax incentives from projects related to the Kyoto Protocol